THE EXPENDITURES FOR THE DEVELOPMENT OF THE MINISTRY OF DEFENSE OF UKRAINE IN THE YEARS 2014-2020 - Marko, I.; Siryi, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article presents and analyses the budget of the Ministry of Defense in the course of the latest years according to data which have been approved by the State budget of Ukraine, its state and perspectives of development, as well as the features that it is influenced by. There’s a presented comparison of the defense budget of the Ministry of Defense of Ukraine in absolute and relative indicators with a consideration for inflation. In every country the sector of defense in a variety of its manifestations happens to be a powerful community that often plays a dominating and crucial role. The aspiration of the government to assure the defense capability of the state is reflected in the adequate establishment of the military budget, the appropriate expenditures for defense purposes, the peculiarities of their implementation under the conditions of a military conflict and its adherence to international norms. Due to the increase in short terms of combat capabilities of the Armed Forces of Ukraine it was possible to stop the illegal armed formations. Yet, the issue of supporting the combat capabilities of our Armed Forces due to the resources and finances used for its purpose remains part of the current agenda. At the current stage of development of Ukraine there are the challenges to increase the defense capabilities of the state, the conduct of reforms of the Armed Forces of Ukraine as well as other military formations in accordance with the state of the art requirements and including the experience obtained in the course of the United Forces Operation, yet also the development of the defense-industrial complex, which is necessary to satisfy the needs of our Armed Forces to the maximum. The successful implementation of the set tasks is in a significant way dependent on the appropriate financial support the basis of which is formed by the expenditures of the state budget. Thus, the issue of dynamics and the structure of the expenditures mentioned as well as the identification of systematic obvious tendencies in the sphere of defense financing are a part of the current agenda, especially under the conditions of the Russian armed aggression against Ukraine.
Keywords: budget, budget appropriations, inflation, cost estimate